BELAJAR MATEMATIKA MELALUI FUN COOKING PADA ANAK USIA DINI - Nadya Pratiwi; Rahma Mujahidatul Islam; Ira Anggraeni (LPPM Universitas Bina Bangsa, 2022)
This paper aims to determine the extent of the influence of fun cooking in improving mathematics learning in early childhood. This article is based on the assumption that learning in early childhood will be more meaningful by playing and having fun for children. In general, mathematics is introduced to the process of counting, measuring, and weighing. Fun cooking was chosen for the method of introducing mathematics to early childhood because it can improve children's mathematical logical abilities in the cooking process such as counting, measuring and weighing food ingredients. The findings from this article are expected to help teachers in implementing fun mathematics learning for early childhood